Clinical outcomes of lupus nephritis patients with different proportions of crescents. (December 2016) - Zhang, W; Yuan, M; Hong, L; Zhou, Q; Chen, W; Yang, S; Yang, Q; Chen, W; Yu, X
Background: The prognostic significance of different proportions of crescents in lupus nephritis (LN) remains unclear. We assessed the long-term prognosis of LN patients with different proportions of crescents. Methods: In this single-center, retrospective cohort study, 788 eligible LN patients were enrolled. The primary endpoint was doubling of baseline serum creatinine and end-stage renal disease; the secondary endpoint was death. Results: There were 406 (51.5%) patients demonstrating crescents at biopsy, and they had more severe baseline status: lower estimated glomerular filtration rate (eGFR), more proteinuria, more severe microscopic hematuria, and higher pathological scores for both activity index (AI) and chronicity index (CIn) (all p  < 0.001, respectively). After a median follow-up period of 56 months (range: 3–172 months), no significant differences were observed in terms of renal or patient survival in these two groups ( p  = 0.188). In LN patients with crescents, patient survival was poorer along with the increase in the proportion of crescents; for crescentic LN, patient survival was 78.9% at five years and 52.6% at 10 years (vs. subgroups of crescent proportion <10%, 10%–19%, 20%–49%: 95.5%, 92.3%, 91.7% at five years; 86.1%, 80.1%, 66.5% at 10 years, respectively, p  = 0.008). Furthermore, there were higher proportions of crescents independently predicted for adverse outcomes of renal progression and mortality ( p  = 0.049) after adjusting for age, sex, baseline eGFR, proteinuria, AI, and CIn in the multivariate Cox proportional hazard model. Conclusion: The overall long-term renal survival of LN patients with and without crescents was comparable. However, a higher proportion of crescents increased the risk for unfavorable outcomes. Therefore, more attention should be paid to the lesions of crescents, and more prospective studies are needed to explore the optimal regimens for LN patients with different proportions of crescents.